The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1111/wre.12378
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific seasonal variation of dormancy and mortality of Phelipanche ramosa seeds

Abstract: Summary Phelipanche ramosa (Branched broomrape) is an obligate root parasitic plant that is a major pest of oilseed rape in France. Knowledge on seed viability and dormancy under field conditions is crucial to understand how to control P. ramosa, but is as yet unknown. Our study aimed to quantify these processes with a 2‐year seed burial experiment. Two genetically distinct populations of P. ramosa were studied, collected on winter oilseed rape (population O) and hemp (population H). Seed mortality was very lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…For example, the P. ramosa tobacco population was reported to be able to reproduce on both oilseed rape and tomato, whereas the tomato lifespan was too short for the P. ramosa oilseed rape population to produce seeds over its life cycle (Gibot-Leclerc et al, 2013). The difference in germination speed between P. ramosa populations observed in our study shows further distinct responses at the intraspecific scale, in addition to distinct seasonal variation of seed dormancy (Pointurier et al, 2019), aggressiveness (Gibot-Leclerc et al, 2013) already reported among these populations. Our study thus suggests that the specialization of P. ramosa probably occurs at least from the first stage of the cycle, that is the underground contact between the seeds of the broomrape and host plant root exudates (Fernández-Aparicio et al, 2011; Gibot-Leclerc et al, 2016; Perronne et al, 2017).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…For example, the P. ramosa tobacco population was reported to be able to reproduce on both oilseed rape and tomato, whereas the tomato lifespan was too short for the P. ramosa oilseed rape population to produce seeds over its life cycle (Gibot-Leclerc et al, 2013). The difference in germination speed between P. ramosa populations observed in our study shows further distinct responses at the intraspecific scale, in addition to distinct seasonal variation of seed dormancy (Pointurier et al, 2019), aggressiveness (Gibot-Leclerc et al, 2013) already reported among these populations. Our study thus suggests that the specialization of P. ramosa probably occurs at least from the first stage of the cycle, that is the underground contact between the seeds of the broomrape and host plant root exudates (Fernández-Aparicio et al, 2011; Gibot-Leclerc et al, 2016; Perronne et al, 2017).…”
Section: Discussionsupporting
confidence: 74%
“…Moreover, these host specificities can also be related to genetic differences between P. ramosa populations, also named pathovars (Le Corre et al, 2014; Stojanova et al, 2019). Thus, the biological life cycle of P. ramosa , the seasonal variation in the dormancy and mortality of the seeds, the aggressiveness of this parasitic plant as well as its germination success can greatly differ between populations of P. ramosa harvested on different host crops (Brault et al, 2007; Gibot-Leclerc et al, 2013; Pointurier et al, 2019; Stojanova et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Some of them will settle and infest the host plant; the others will be killed by plant-derived allelochemicals (Cimmino et al 2018;Qasem and Issa 2018). Seeds outside the rhizosphere are dormant, and most of them will survive for several years in the soil and contribute to what is called the weed seed bank (Haring and Flessner 2018;Pointurier et al 2019). In parallel, a host of small animals and diversified microorganisms also lives in the soil.…”
Section: Introductionmentioning
confidence: 99%